Histomorphometric Features of Deltoid Muscle (Musculus Deltoideus) in the Mouflon (Ovis ammon musimon Pal.) and Domestic Sheep - Nenad Nedeljkovic; Gabi Dumitrescu; Liliana Petculescu-Ciochina; Ioan Bencsik; Dorel Dronca; Eliza Simiz; Marioara Nicula; Adela Marcu; Valeriu Carabă; Tiberiu Iancu; Nicolae Păcală (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of this study was to determine histomorphometry of the skeletal muscle in rams from the Tigaie breed and mouflon males (Ovis ammon musimon Pal.) knowing that, in addition to a variety of factors, both the fiber thickness and muscle fascicles influence the meat quality. The study was conducted on the deltoid muscle fragments taken from five individuals of the each species. The muscle samples were processed according to the method of embedded in paraffin, sectioned to a thickness of 5 µm and stained with Mallory's trichrome method. From the histomorphometric analysis resulted that in mouflon, the average area of muscle fascicles is larger, as compared with the ram (p <0.05), the ratio between the fascicles muscle area and the interfascicular connective tissue being 2.939:1 for  mouflon and 1,624:1 for ram. Also, in mouflon the muscle fibers are thicker, the area and perimeter registering an average value of 486.60 μm2, respectively 82.83 μm while in ram, the area of the muscle fibers is 281.56 μm2 and the perimeter of 62.92 μm (p <0.001). The amount of interfibrillar connective tissue is higher in ram (p<0.05) and the ratio between the muscular fibers area and interfibrillar connective tissue area was 1.649:1 in mouflon and 1.451:1 in ram (p<0.05).